Chlamydiaceae-Like Bacterium in Wild Magellanic Penguins (Spheniscus magellanicus) - Lucía Gallo Vaulet; Ralph Eric Thijl Vanstreels; Luciana Gallo; Andrea Carolina Entrocassi; Laura Peker; Gabriela S. Blanco; Maria Virginia Rago; Marcelo Rodriguez Fermepin; Marcela M. Uhart (Diversity, 2022)
The family Chlamydiaceae is comprised of obligate intracellular bacteria, some of which are significant pathogens of humans and domestic animals. Magellanic penguins (Spheniscus magellanicus) are susceptible to Chlamydia psittaci outbreaks in captivity, and serological surveys detected antibodies against C. psittaci (or antigenically similar organisms) in wild populations of this species. To investigate the occurrence of Chlamydiaceae in wild Magellanic penguins, 167 cloacal swabs were collected from apparently healthy individuals at four breeding colonies along the coast of Chubut, Argentina. Real-time PCR revealed the presence of DNA from Chlamydiaceae-like bacteria in 61 cloacal swabs (36.5%). Detection did not correlate to nutritional status or to meaningful hematological abnormalities. Isolation in monkey kidney cells was unsuccessful, but DNA sequences for the 16S–23S rRNA region were obtained from one sample. Phylogenetic analysis showed a close relationship to unidentified Chlamydiaceae-like bacteria found in chinstrap penguins (Pygoscelis antarcticus) in Antarctica and seagulls in France and the Bering Sea, and to Chlamydiifrater spp. isolated from flamingos in France. Further studies are necessary to clarify the taxonomy and investigate the epidemiology, pathogenicity, and zoonotic potential of this group of Chlamydiaceae-like bacteria.